2010
DOI: 10.1161/circoutcomes.109.911461
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Events and All-Cause Mortality in Patients Treated With Thiazolidinediones in a Managed-Care Population

Abstract: Background-This study directly compares risk of acute myocardial infarction (AMI), acute heart failure (AHF), or all-cause death among pioglitazone-and rosiglitazone-treated patients in a managed-care population. Methods and Results-Patients Ն18 years of age, newly initiated on rosiglitazone or pioglitazone between January 1, 2001, and December 12, 2005, were included. The date of the first pharmacy claim for rosiglitazone or pioglitazone was defined as index date. Patients were excluded if they had Ͻ1 year co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Similarly, information on future exposures and particular events occurring during follow-up should not inform cohort inclusion or exclusion criteria. Several studies included or excluded patients on the basis of information collected during follow-up, such as the use of insulin after cohort entry [6,24,32,34], use of glucose-lowering combinations [34,40] or switching to other glucose-lowering therapy [24,41]. By conditioning inclusion or exclusion criteria on the basis of future information, these studies have the potential for bias arising from immortal time acting through selection.…”
Section: Incorrect Consideration Of Temporal Sequencing In Healthcarementioning
confidence: 99%
“…Similarly, information on future exposures and particular events occurring during follow-up should not inform cohort inclusion or exclusion criteria. Several studies included or excluded patients on the basis of information collected during follow-up, such as the use of insulin after cohort entry [6,24,32,34], use of glucose-lowering combinations [34,40] or switching to other glucose-lowering therapy [24,41]. By conditioning inclusion or exclusion criteria on the basis of future information, these studies have the potential for bias arising from immortal time acting through selection.…”
Section: Incorrect Consideration Of Temporal Sequencing In Healthcarementioning
confidence: 99%
“…Other publications have reported quite different fi ndings. In a retrospective cohort study, Wertz et al directly compared Avandia and Actos and found no signi fi cant differences in their risk of AMI [12], acute heart failure or death, fi ndings echoed by Bilik et al [13]. The Wellpoint Study, using an insurance company database and published in August 2010, appeared to show no difference between Avandia and Actos regarding key cardiac adverse events, including heart attack.…”
Section: Continued Discussion In the Literature Of The Cardiovascularmentioning
confidence: 99%
“…111 A recent casematching cohort study suggests that the risks of MI, heart failure or death are about the same in diabetic patients taking either pioglitazone or rosiglitazone, challenging a number of reports that the cardiovascular risks differ between the 2 drugs. 112 …”
Section: Clinical Trialsmentioning
confidence: 99%